2021
DOI: 10.1051/ocl/2021005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of EU legume value chains from the H2020 LegValue project: What insights for organic value chains?

Abstract: This paper presents the results of a legume-based value chain analysis based on twenty-seven case studies in the H2020 LegValue project and discusses those relating to organic legume-based value chains. The analysis aims to illustrate the diversity of legume-based value chains and to discuss the conditions by which they can successfully meet the growing demand for legumes in the EU. The research is based on a qualitative survey of the value chain stakeholders in the case studies. Regarding organic legume-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The value chains initiated to satisfy the demand of the organic market have the downstream farmers as the main actors. While the approach of value chains toward the development of organic agriculture has as main actors those located upstream from the farmers [45], regarding the distribution of economic benefits, farmers often have the smallest margins compared to intermediaries [26]. Value chain research in organic agriculture in Europe is limited.…”
Section: Value Chain Upgradationmentioning
confidence: 99%
“…The value chains initiated to satisfy the demand of the organic market have the downstream farmers as the main actors. While the approach of value chains toward the development of organic agriculture has as main actors those located upstream from the farmers [45], regarding the distribution of economic benefits, farmers often have the smallest margins compared to intermediaries [26]. Value chain research in organic agriculture in Europe is limited.…”
Section: Value Chain Upgradationmentioning
confidence: 99%
“…Likewise, (Ganguly and Gulati 2022) in India revealed that pulses value chains development was helpful in addressing the observed protein gap in the diets and also improve the livelihood of the smallholder farmers. However, Smadja and Muel (2021) contended that in developing countries structural bottlenecks regarding pulses value chains development varied along with regions and countries. Thus, country specific or region-specific investigation is required for effective and robust value chain development.…”
Section: Introductionmentioning
confidence: 99%